Performance estimation and synergetic role of caffeine in increasing efficacy of Bacillus thuringiensis var. kurstaki on Plodia interpunctella hübner (Lepidoptera: Pyralidae) - Ziaee, Azam; Dehnavi, Lida Dehghan; Khormizi, Mehdi Zare; Goldasteh, Shila; Farazmand, Hossien; Hanley, Guy A.; Latibari, Minoo Heidari (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
The Indian meal moth, Plodia interpunctella (Hübner) is a widespread and serious pest of stored products. The aim of this study was to evaluate the effectiveness of Bacillus thuringiensis var. kurstaki, and its synergistic effect with caffeine, in the control of P. interpunctella. The minimum and maximum lethal concentrations (LC) of B. thuringiensis for first instar larvae control, respectively were 65 ppm and 7500 ppm. The LC50 for the first instar stage of larvae was 637.87 ppm. When first instar larvae are fed a diet which contained LC50 of both B. thuringiensis and caffeine, an increased synergistic interaction in terms of mortality was found. The mixture of minimum effective concentrations of 65 ppm bacteria and 4000 ppm of caffeine have resulted in 95% mortality after 144 h, whereas caffeine and bacteria alone caused 10% and 20% mortality, respectively.